2015
DOI: 10.4172/2161-0991.1000155
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes about Organ Donation among Medical Students in Egypt: A Questionnaire

Abstract: Introduction: Organ transplantation (OT) is life-saving for patients with failing organs. Shortage of donor organs can be solved by raising the willingness of the population to donate organs. Health-care professionals have a fundamental role in raising the public awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 31 publications
(48 reference statements)
6
25
0
1
Order By: Relevance
“…In agreement with this Hamed et al (15) reported absence of association between gender and attitude of medical students toward OD. In contrast, many reports concluded that female gender was significantly associated with positive attitude towards OD (27)(28)(29).…”
Section: Results:-supporting
confidence: 81%
See 2 more Smart Citations
“…In agreement with this Hamed et al (15) reported absence of association between gender and attitude of medical students toward OD. In contrast, many reports concluded that female gender was significantly associated with positive attitude towards OD (27)(28)(29).…”
Section: Results:-supporting
confidence: 81%
“…Similar poor knowledge was reported in Pakistan where only 23% of participants knew that organs can come from both living and cadaver bodies (17). Actually, inadequate knowledge and vague conception of brainstem death always had a negative effect on OD (15). A survey on Sweden ICU nurses highlighted that they didn't trust brain death diagnosis (18).The current study also revealed that the overall perceptions about OD did not differ significantly by educational level, gender, or the family income.…”
Section: Results:-supporting
confidence: 73%
See 1 more Smart Citation
“…In this context the results are not in agreement with those reported by Hamed H et al, from Egypt where 83% of the respondents thought there was no law regulating organ donation or didn't hear or read about the law. 14 Further the information about organ donation card was found to be very dismal as only 19.29% of the respondents knew where to obtain this card. Also 80.71% of them didn't know that organ donation card can be substituted as an emergency card.…”
Section: Discussionmentioning
confidence: 98%
“…6 Knowledge and attitude of health care providers towards organ donation plays a major role in promoting the concept among population. 7 The general population and the student population in particular, need to be educated about transplantation and the need to accept the commitment to donate organs. Therefore, the present study was designed to assess and compare the knowledge, attitude and practice regarding organ donation and transplantation, among medical students, based on gender, year of the course and religion.…”
Section: Introductionmentioning
confidence: 99%